2020
DOI: 10.1016/j.artd.2020.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Day Outcomes After Bilateral Total Hip Arthroplasty in a Nationwide Cohort

Abstract: Background: Approximately 42% of patients with end-stage osteoarthritis have bilateral disease. Although bilateral total hip arthroplasty (THA) is physiologically demanding, certain patients may benefit from simultaneous rather than staged bilateral procedures. This study examines the intraoperative differences and 30-day outcomes in patients receiving bilateral THA compared with those who underwent unilateral THA. Methods: Patients undergoing THA were selected from the National Surgical Quality Improvement Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Results showed an average age under 60 years for THA and under 70 years for TKA. Taking into account the physiologic demands of patients undergoing simultaneous bilateral arthroplasty, previous studies have pointed out that they are generally younger, have lower BMI and less comorbidities than patients undergoing unilateral or staged bilateral arthroplasty [23][24][25][26]. Our results showed that the overall male/female ratio was almost equal for THA over the study period.…”
Section: Discussionsupporting
confidence: 50%
“…Results showed an average age under 60 years for THA and under 70 years for TKA. Taking into account the physiologic demands of patients undergoing simultaneous bilateral arthroplasty, previous studies have pointed out that they are generally younger, have lower BMI and less comorbidities than patients undergoing unilateral or staged bilateral arthroplasty [23][24][25][26]. Our results showed that the overall male/female ratio was almost equal for THA over the study period.…”
Section: Discussionsupporting
confidence: 50%
“…Patients who had SBTHA were younger and had less comorbidities than those who had UTHA. However, despite this difference in the groups, transfusion and deep infection rates were significantly higher for SBTHA 19 .…”
Section: Primary Outcomesmentioning
confidence: 76%
“…In 2020 Morton et al compared SBTHA and UTHA 19 . Patients who had SBTHA were younger and had less comorbidities than those who had UTHA.…”
Section: Primary Outcomesmentioning
confidence: 99%
“…However, other authors found no significant differences concerning thromboembolic events, cardiovascular complications, blood loss or transfusion rate [ 2 , 11 , 12 ]. Unfortunately, most of the studies only included patients with American Society of Anesthesiologists (ASA) scores of I or II [ 13 17 ] or lacked any evaluation of early or mid-term functional outcomes [ 1 , 2 , 8 , 14 , 18 ].…”
Section: Introductionmentioning
confidence: 99%